Laparoscopic resection of lower rectal cancer with telescopic anastomosis without abdominal incisions - Li, Shi-Yong (World J Gastroenterol, 2015)
AIM: To assess laparoscopic radical resection of lower rectal cancer with telescopic anastomosis through transanal resection without abdominal incisions. METHODS: From March 2010 to June 2014, 30 patients (14 men and 16 women, aged 36-78 years, mean age 59.8 years) underwent laparoscopic radical resection of lower rectal cancer with telescopic anastomosis through anus-preserving transanal resection. The tumors were 5-7 cm away from the anal margin in 24 cases, and 4 cm in six cases. In preoperative assessment, there were 21 cases of T(1)N(0)M(0) and nine of T(2)N(0)M(0). Through the middle approach, the sigmoid mesentery was freed at the root with an ultrasonic scalpel and the roots of the inferior mesenteric artery and vein were dissected, clamped and cut. Following the total mesorectal excision principle, the rectum was separated until the anorectal ring reached 3-5 cm from the distal end of the tumor. For perineal surgery, a ring incision was made 2 cm above the dentate line, and sharp dissection was performed submucosally towards the superior direction, until the plane of the levator ani muscle, to transect the rectum. The rectum and distal sigmoid colon were removed together from the anus, followed by a telescopic anastomosis between the full thickness of the proximal colon and the mucosa and submucosal tissue of the rectum. RESULTS: For the present cohort of 30 cases, the mean operative time was 178 min, with an average of 13 positive lymph nodes detected. One case of postoperative anastomotic leak was observed, requiring temporary colostomy, which was closed and recovered 3 mo later. The postoperative pathology showed T(1)-T(2)N(0)M(0) in 19 cases and T(2)N(1)M(0) in 11 cases. Twelve months after surgery, 94.4% patients achieved anal function Kirwan grade 1, indicating that their anal function returned to normal. The patients were followed up for 1-36 mo, with an average of 23 mo. There was no local recurrence, and 17 patients survived for > 3 years (with a survival rate of 100%). CONCLUSION: Laparoscopic radical resection of lower rectal cancer with telescopic anastomosis through transanal resection without abdominal incisions is safe and feasible.